EFFECTS OF POLYGON TRAINING ON AEROBIC CAPACITY VO2MAX IN MALE CHILDREN - Adis Bekić; Benjamin Alić; Almir Atiković; Zerin Emić (Sport Scientific And Practical Aspects, 2025)
Many children become less active as they age which increases their risk of developing of chronic conditions. Traditional forms of physical activity may not be optimal for them. There is a need for more attractive form of training to try and increase physical activity levels and improve the fitness of children. The aim of this study was to determine the effects of performing polygon training on measures of functional capabilities. The subjects (13 years +/- 6 months) old boys were randomly allocated to one of two groups: trampoline training group (EG, N=33) and control group (CG, N=29) to examine effects of 15-week polygon training (1 time per week). Results of study shows that additional programme based on overcoming polygons in combination wih regural classes of physical education gives positive effects on improving of functional capabilities VO 2 max. Polygon training is an effective intervention to improve functional capabilities.